Examining the Societal and Legal Landscape of Drug Abuse Awareness: A Comprehensive Survey among University Students - Naresh Prajapati, Deepak Kumar, Smriti Rai, Dharmendra Kumar Kumawat (Journal of Informatics Education and Research, 2023)
A recent study of 51 university students from the Central University of Punjab revealed a growing global trend of reliance on pharmaceuticals. The study aimed to assess drug addiction awareness among students and found that while some were aware of the negative impacts on physical and mental health, there is still room for improvement. Socio-cultural factors such as familial background and media portrayals of drug use were found to influence students’ knowledge of addiction. Legal issues, such as opinions on law enforcement activities and understanding drug-related laws and regulations, were also examined. The study highlights the need for continuous improvement in drug addiction awareness among university students, taking into account socio-cultural and legal contexts.